Scaredy Bear - Griffiths Neil (United Kingdom Red Robin Books, 2014)
Baby bear loved the warmth and safety of the cave where he lived with his mom. However, like all baby bears the time had come when he had to leave and explore the world outside. But was there really anything to be scared of?